The Role of Friendship in Percy Jackson and the Olympians TV Series: A Lacanian Psychoanalytic Study of Identity and Emotional Development - Adala Shiva; Prayudias Margawati (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
This study explores the role of friendship in shaping the psychological development of the main character in the Percy Jackson and the Olympians TV series through the lens of Lacan’s psychoanalytic theory. The research aims to examine how Percy’s relationships, particularly with the main character’s friends, contribute to identity formation and emotional growth. This study adopts a qualitative and thematic textual analysis approach, guided by Lacanian psychoanalytic theory. The data collection involved close reading and repeated viewing of key episodes. By applying Lacan’s key concepts, including the Mirror Stage, desire, lack (manque), and the triadic orders of the Imaginary, the Symbolic, and the Real, this study analyzes how the series portrays friendship as a vital medium through which the main character navigates his sense of self and subjectivity. The findings suggest that friendship functions not only as emotional support but also as a reflective structure that drives the main character’s evolving identity. The Symbolic becomes central when friendships provide moral language and social recognition, especially through Annabeth’s and Grover’s dialogue. Moreover, the study reveals that the series subverts conventional heroic narratives by emphasizing psychological depth and emotional dependency, positioning friendship as central to the hero’s journey. This analysis contributes to a deeper understanding of how contemporary screen adaptations can integrate psychoanalytic dimensions into character development.